2004
DOI: 10.1074/jbc.m313916200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-dependent Protein Kinase Phosphorylates Merlin at Serine 518 Independently of p21-activated Kinase and Promotes Merlin-Ezrin Heterodimerization

Abstract: Mutations in the NF2 tumor suppressor gene encoding merlin induce the development of tumors of the nervous system. Merlin is highly homologous to the ERM (ezrinradixin-moesin) family of membrane/cytoskeleton linker proteins. However, the mechanism for the tumor suppressing activity of merlin is not well understood. Previously, we characterized a novel role for merlin as a protein kinase A (PKA)-anchoring protein, which links merlin to the cAMP/PKA signaling pathway. In this study we show that merlin is also a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 44 publications
4
114
0
1
Order By: Relevance
“…Phosphorylation of Merlin at Ser518 was previously reported to play an important role in regulating Merlin tumor suppressor activity (Shaw et al, 2001;Alfthan et al, 2004;Jin et al, 2006a). Interestingly, the interaction between Merlin and VprBP is independent of Ser518 phosphorylation of Merlin (data not shown), suggesting that the Merlin-VprBP interaction might represent a new means for Merlin regulation in vivo.…”
Section: Identification Of Vprbp and Ddb1 As Merlin-associated Proteinsmentioning
confidence: 84%
See 1 more Smart Citation
“…Phosphorylation of Merlin at Ser518 was previously reported to play an important role in regulating Merlin tumor suppressor activity (Shaw et al, 2001;Alfthan et al, 2004;Jin et al, 2006a). Interestingly, the interaction between Merlin and VprBP is independent of Ser518 phosphorylation of Merlin (data not shown), suggesting that the Merlin-VprBP interaction might represent a new means for Merlin regulation in vivo.…”
Section: Identification Of Vprbp and Ddb1 As Merlin-associated Proteinsmentioning
confidence: 84%
“…Phosphorylation of a C-terminal serine (S518) by p21-activated kinase (PAK)-or cAMP-dependent protein kinase A weakens Merlin's self-association and is believed to inactivate its growth-suppressing activity. On the other hand, the phosphatase MYPT-1-PP1-d activates the tumor suppression activity of Merlin through S518 dephosphorylation, which subsequently inhibits the Ras/ERK (extracellular signal-regulated kinase) pathway (Shaw et al, 2001;Alfthan et al, 2004;Jin et al, 2006a). In addition, Merlin can also be regulated at the protein level by growth arrest stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we demonstrate that Ser518 phosphorylation results in impaired merlin Nterm/C-term folding as well as altered interactions with critical merlin-associated proteins. Recently, Alfthan et al (2004) demonstrated that protein kinase-A (PKA) induces merlin phosphorylation on both N-and C-terminal residues in vitro and in vivo Like PAK, PKA can phosphorylate merlin at Ser518, but unlike PAK, also results in merlin phosphorylation on Ser66 in the N-terminal domain. In their study, they show that merlin can be phosphorylated by PKA in cells, in which PAK activity was suppressed, indicating that these two kinases likely function independently.…”
Section: Discussionmentioning
confidence: 99%
“…This ezrin phosphorylation requires upstream p38 MAP kinase activation but is unlikely to be mediated directly by p38 MAP kinase, because ezrin threonine 567 lacks the proline residues that are typically present within p38 MAP kinase targets. Rho kinase, PKA, and some PKC isoforms have been reported to phosphorylate ezrin or other ERM-related proteins (9,11,12,43). However, rho kinase (27) or PKA inhibition does not prevent NHE3 activation after initiation of Na ϩ -glucose cotransport, and both PKA and PKC activation are well known to reduce NHE3 activity and surface expression (30,44).…”
Section: Akt Inhibition Prevents Ezrin Phosphorylation After Initiatimentioning
confidence: 99%